The aids and its contradictions: social representations of its attendance and treatment for the professionals and patients - Ribeiro, Cristiane G.; Castanha, Alessandra R.; Coutinho, Maria P.L.; Saldanha, Ana A.W. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the aids brought obtains the necessity of reformularization of the medical authority structure, imposing the necessity of attention to thepatient as a whole and not only to examine the sick organ. Objective: to understand the displayed subject better, it makes important to know thesocial representations of the professionals and patients concerning the attendance and treatment of the aids. Methods:the sample was composed for77 professionals who work directly in the context of the aids (professionals of Health and professionals of Human) and 41 positive HIV patients(male and female). Was used the Words Free Association technique, analyzed through Tri-Deux-Mot software (version 2.2) by the correspondencefactorial analysis. Results: the results (explaining 73,8% of total variance) showed consensual universes, as well as specificities in the representationsof each category. Was observed a tendency to the practice of the biomedical model that it permeates in such a way as much the professionals’ repre-sentation as patients one. Conclusion: emerged new forms of anchorage of aids, not only in the sexually transmissible disease or the great plagues,but also in the psycho-affective disturbances, including depression. In all of the studied aspects, aids appears as contradictory and antagonistic pheno-menon, naturalized as ugly and threatening and at the same time as life source and hope.